Caenorhabditis elegans-Based Aspergillus fumigatus Infection Model for Evaluating Pathogenicity and Drug Efficacy - Ahamefule, Chukwuemeka Samson; Qin, Qijian; Odiba, Arome Solomon; Li, Siqiao; Moneke, Anene N.; Ogbonna, James C.; Jin, Cheng; Wang, Bin; Fang, Wenxia (Frontiers in Cellular and Infection Microbiology, 2020)
Aspergillus fumigatus is the most reported causative pathogen associated with the increasing global incidences of aspergilloses, with the health of immunocompromised individuals mostly at risk. Monitoring the pathogenicity of A. fumigatus strains to identify virulence factors and evaluating the efficacy of potent active agents against this fungus in animal models are indispensable in current research effort. Caenorhabditis elegans has been successfully utilized as an infection model for bacterial and dimorphic fungal pathogens because of the advantages of being time-efficient, and less costly. However, application of this model to the filamentous fungus A. fumigatus is less investigated. In this study, we developed and optimized a stable and reliable C. elegans model for A. fumigatus infection, and demonstrated the infection process with a fluorescent strain. Virulence results of several mutant strains in our nematode model demonstrated high consistency with the already reported pathogenicity pattern in other models. Furthermore, this C. elegans-A. fumigatus infection model was optimized for evaluating the efficacy of current antifungal drugs. Interestingly, the azole drugs in nematode model prevented conidial germination to a higher extent than amphotericin B. Overall, our established C. elegans infection model for A. fumigatus has potential applications in pathogenicity evaluation, antifungal agents screening, drug efficacy evaluation as well as host-pathogen interaction studies.